Kualitas Pelayanan Publik Di Dinas Kependudukan dan Pencatatan Sipil Kabupaten Minahasa - Teresa O. Tumbelaka; Sisca B. Kairupan; Brain Fransisco Supit (CV. Kurnia Grup, 2026)
This study aims to identify and describe the quality of public services at the Department of Population and Civil Registration of Minahasa Regency, and to determine the factors that hinder the service process in the Marriage Registration Division of the Department of Population and Civil Registration of Minahasa Regency. The approach used in this research is a qualitative approach. The number of informants in this study was 7 people. Data collection techniques included observation, interviews, and documentation. Data analysis was carried out through data reduction, data presentation, and conclusion drawing. The results of this study indicate that services at the Department of Population and Civil Registration of Minahasa Regency, particularly in the Marriage Registration Division, are not yet fully optimal and maximal: Facilities and infrastructure are still inadequate. Services are often delayed when unexpected issues occur, such as power outages, which cause service facilities to be unable to function and hinder employees in carrying out services. Services are not yet optimal due to delays in employee response, often caused by network disruptions from the central system and the absence of staff in the office or when they are on external assignments, which hampers the service process for the community